(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study provides a theoretical and scientific analysis of modern methodological approaches to developing natural science literacy in general secondary education schools. The research examines the content and pedagogical significance of competency-based, systems-activity, integrative, inquiry-based, and student-centered approaches. In addition, the study explores the scientific foundations of organizing the educational process based on the HPL (How People Learn) model, substantiating the importance of active, contextual, and socially interactive learning environments in fostering students’ natural science literacy.